Interdisciplinary Approaches to Contemporary Economic Issues: Law, Policy, and Digital Transformation - Hossein Askari Mattson (PT. Islamic Research Publisher, 2025)
The accelerating pace of globalization, technological innovation, and economic uncertainty has fundamentally reshaped contemporary economic systems, generating complex legal, regulatory, and governance challenges that cannot be adequately addressed through single-disciplinary perspectives. This study aims to examine how interdisciplinary approaches integrating law, public policy, and digital transformation contribute to resolving contemporary economic issues while promoting sustainable, inclusive, and resilient economic development. This study employs a qualitative research approach by examining scholarly publications, international policy reports, and regulatory frameworks related to digital economies, economic governance, innovation policy, and legal adaptation. Data were analyzed using thematic content analysis to identify recurring patterns, conceptual relationships, and emerging interdisciplinary frameworks. The findings reveal that effective responses to contemporary economic challenges require dynamic legal systems capable of adapting to technological disruption, evidence-based public policies that balance innovation with social protection, and digital transformation strategies that strengthen institutional transparency, market efficiency, and economic inclusion. Furthermore, the study demonstrates that interdisciplinary governance enhances regulatory coherence, improves stakeholder collaboration, and facilitates the development of adaptive policy mechanisms for addressing digital finance, platform economies, data governance, and sustainable economic growth. The analysis also indicates that integrating legal certainty with technological innovation is essential for mitigating regulatory fragmentation and fostering long-term economic resilience in both developed and emerging economies. This research contributes to the growing body of interdisciplinary scholarship by proposing an integrated analytical framework that bridges legal studies, economic policy, and digital governance within a unified perspective. The framework provides both theoretical insights and practical implications for policymakers, legal practitioners, and researchers seeking to formulate responsive economic regulations and governance models capable of addressing the evolving challenges of the digital economy in the twenty-first century.